Structure preserving formulation of high viscous fluid flows - Olesen, Kennet (Technical Report Mechanical Engineering, 2014)
This report contains the progress status of the PhD project titled “Structure preserving formulation of high viscous fluid flows”. It describes the first ideas to a numerical scheme, which conserves mass and momentum in a discrete sense. It is based on spectral expansion polynomials, and it is thought to be applicable to arbitrary constitutive fluid models.